Похибки виведення балiстичних ракет - Карачун, В.В.; Кладун, О.А. (Видавничий дім "Академперіодика" НАН України, 2008)
The errors of a gyroscopic integrator of linear accelerations are analyzed in model terms. The degree of influence of the penetrable acoustic radiation is set on the technical descriptions of wares.